El crecimiento económico del Ecuador: un análisis exhaustivo en la formación bruta de capital y recursos naturales, periodo 1970-2019 - Aguinsaca Robalino, Mariela Lourdes (2023)
Economic growth at the local level has been immersed in constant behaviors, presenting a drop of 7.8% during the year 2020. Based on the economic characteristics of Ecuador, the research had the general objective of analyzing the impact of the gross capital formation and natural resources on the economic growth of Ecuador, during the period 1970-2019. The data used for the purposes of the investigation were taken from the World Development Indicator of the World Bank, therefore, to fulfill the purpose of the investigation, the Cochrane-Orcutt model and a vector autoregressive model (VAR) were applied. The results prove that the gross formation of capital and the rent of natural resources contribute to the economic growth of Ecuador, therefore, the improvements of the same imply a growing yield over time, likewise, the positive incidence of the EAP is attributed towards growth, in addition to the presence of a long-term relationship between them. In this way, it is proposed to apply programs and at the same time projects that generate incentives to national companies in both the public and private sectors, as well as encourage the sustainable use of the natural resources that it possesses.